Pertemuan Konsultan Masyarakat Perencanaan Teknis di Salobunne Kabupaten Soppeng - Tambaru Tambaru; Rafli Yunianto Pratama; Nusbih Ismail; Rio Udaya; Siti Munawaroh; Delma Pratisa; Afifah Masruniwati (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Community Consultation Meeting (PKM) for the Technical Planning of the Salobunne Irrigation Area (D.I Salobunne) in Soppeng Regency represents a participatory approach to the preparation of irrigation infrastructure development plans. This activity aimed to provide local communities with information about the proposed irrigation improvement plans and to collect input, suggestions, and recommendations from various stakeholders in the region. The meeting was held at the Village Hall of Tellulimpoe, Marioriawa District, and was attended by representatives from local government, technical consultants, community leaders, and farmer organizations such as P3A and GP3A. The forum served as a platform for communication between technical implementers and the community to ensure that the planning aligns with real conditions and local needs. The outcome of the meeting demonstrated positive collaboration in realizing a participatory, appropriate, and sustainable irrigation planning system.